Implementasi Low Power pada Alat Pengisian Penampungan Air Otomatis menggunakan Metode Sleep Mode berbasis Arduino Uno - Ahmar Fauzan Sira; Mochammad Hannats Hanafi Ichsan; Agung Setia Budi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Water is a natural resource that is needed by all living things. It is appropriate that we have to preserve these resources. Simply by using water as necessary, it is already preserving the water on earth. But as a human being who doesn't escape mistakes, he must have experienced where he forgot to turn off the water pump when filling the water reservoir at home so that the water was wasted. For this reason, this research was carried out. The system consists of Arduino Uno as processing, Ultrasonic Sensor HC-SR04 to read water level and Relay to turn on and off the water pump. And also the system created will apply low powering using the sleep mode method, so that when filling the water reservoir it takes a relatively long time. This tool does not continue to read the water level, but will enter sleep within the specified timeframe. So this tool will only be active when the water level in the reservoir has been detected as running out or full, so that it will optimize the power used. After the system is designed and tested, the average power used by the system before applying low power is 83.88 mA when the water pump is on and 24.18 mA when the pump is off. When compared after applying low power, the system is able to make 13.14% efficient when the pump is on and 53.73% when the pump is off.